Home Industry dalam Menyerap Tenaga Kerja Wanita di Desa Cimari - Tati Heryati; Rita Patonah; Nur Rizqi Arifin (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2023)
The existence of the Home Industry in Cimari Village has succeeded in creating job opportunities for the community, especially those in the Cimari Village area. The existence of forty home industries spread across five hamlets, mostly engaged in the processing of light snacks. The home industry has succeeded in absorbing a workforce that is mostly dominated by female workers. The home industry requires the existence of female workers because there are several work tasks that are very relevant to the character of a woman, namely being thorough and tidy. Female workers are generally in charge of packing and product manufacturing. This study aims to find out the role of the home industry in absorbing female workers in the Cimari Village area. The method used in this research is a descriptive method with a qualitative approach. Data collection techniques were carried out through observation and interviews. The research subjects are female workers who are scattered in the home industry in Cimari Village. The conclusion from this study is that the existence of the home industry plays a role in absorbing female workers in Cimari Village.